The Argumentation in the Message of Sahl Bin Haroun to his Cousins of AL – Rahboon - Al- Molqi, Ahmad Abdalkareem (Arab Journal for Sciences and Research Publishing, 2020)
The research aimed to study the persuasive and Argumentation mechanisms followed by Sahl Bin Haroun in his message to his cousins, when they blasphemed his doctrine in miserliness, by defending his position on miserliness, generosity, and economics. The research used the descriptive and analytical method based on linking what was stated in the letter of Sahl Bin Haroun to the social reality experienced by Bin Haroun. The research found that the message of Sahl ibn Harun, a text of Hajjaji par excellence, took the character of persuasive, argumentative, persuasive argument, dialogue, simplification of arguments, presentation of claims, and brilliantly violating them to his opponents from his cousins.
Keywords: Argumentation; A letter from Sahl ibn Harun; The Rahbun family; Pragmatics